Escolha do melhor índice de temperatura e umidade e efeito das estações do ano e da idade sobre as variáveis fisiológicas e hematológicas de bezerros leiteiros mestiços - Nascimento, Fernanda Gatti de Oliveira (2018)
First, the aim of the study was to determine among nine temperature-humidity index (THI) equations, the one that best represents the effects of heat stress on crossbred dairy calves reared in a tropical environment. Twelve male and female calves, aged 20 to 60 days, and raised in a tropical pen were evaluated. Respiratory and heart rates, rectal, body surface, dry bulb and wet bulb temperatures were quantified in the morning and afternoon. Nine THI equations were calculated. The THI sensible heat-based equation presented the highest correlation with physiological variables, therefore it is the equation that best represents the effects of meteorological conditions on the thermal equilibrium of crossbred dairy calves reared in a tropical environment. The second research evaluated the influence of seasons and age on the physiological and hematological variables of crossbred dairy calves raised outdoors in a tropical environment. Forty-two male and female calves were evaluated from July 2016 to July 2017, when the calves were of 2, 15, 30, and 60 days of age. Respiratory and heart rates, rectal, body surface, dry bulb and wet bulb temperatures were quantified in the morning, and THI sensible heat-based were calculated. Subsequently, three milliliters of blood were collected from each calf to perform the hemogram. The day before the calves were evaluated, thermal environment data were collected to verify whether there were cyclic periods of heat stress. The mean air temperature ranged from 19 °C to 22.1 °C, and the highest THI value of 68 occurred in the summer mornings. In the afternoon, the maximum air temperature ranged from 27.5 °C to 29.7 °C. In autumn, respiratory and heart rates and body surface temperature were higher in 2-day-old calves than in other ages. The body surface temperature of 60-day-old calves was higher in spring and summer than in autumn. Rectal temperature remained in the normal range throughout the study period. Season did not influence the erythrogram and plaquetogram. The values for red blood cells, MCV, MCHC, RDW, platelets, and MPV varied among the calf ages. Season did not influence the values of leukocytes, monocytes, lymphocytes, or N/L ratio; however, band neutrophils and eosinophils varied among seasons. Band neutrophils and monocytes were not altered by age, whereas leukocyte, segmented neutrophils, eosinophils, lymphocytes, and N/L ratio values varied with age among the calves.